Project learning practice of quantity surveying firms - Abdul-Rahman, Hamzah; Alashwa, Ali Mohammed; Jamaludin, Zatil Hidayah (2010)
Quantity surveying firms in Malaysia are aware on the importance of learning from construction projects.However, it is not known how these firms can practice and implement this notion successfully.This paper aims at identifying the methods of learning as being practiced by these firms, the success factors and the barriers of project learning implementation.To achieve these aims a questionnaire survey followed by an interview were conducted.The interview used to validate and expand the results of the survey. The results indicated that on-the-job training is the preferable method to learn from project.Top management support was found to be one of the key factors of project learning success. In addition, top management support and employee participants are the main enablers / barriers of project learning implementation.